Book Reviews. Issue 1 (1st August 2021) - Unknown
Abstract : Anna Artwinska and Agnieszka Mrozik, eds., Gender, Generations, and Communism in Central and Eastern Europe and Beyond, New York: Routledge, 2020, 352 pp., £120.00 (hardback), ISBN: 978-0-36742-323-0. CLIO: Femmes, Genre, Histoire 48, no. 2, "Genre et espace (post-)ottoman" (Gendering the [post-]Ottoman world), Paris: Editions Belin/Humensis, 2018, 328 pp., €21.00 (paperback), ISBN: 97-2-410-01429-7. Lisa Greenwald, Daughters of 1968: Redefining French Feminism and the Women's Liberation Movement, Lincoln: University of Nebraska Press, 2019, 426 pp., 64.50 (hardback), ISBN: 978-1-496-20755-5. Gal Kirn, The Partisan Counter-Archive: Retracing the Ruptures of Art and Memory in the Yugoslav People's Liberation Struggle, Berlin: De Gruyter, 2020, 309 pp., 43 illustrations, €86.95 (hardback), ISBN: 9783110681390. Milena Kirova, Performing Masculinity in the Hebrew Bible, Sheffield: Sheffield Phoenix Press, 2020, 212 pp., €75.00 (hardback), ISBN 978-1-910928-77-6. Andrea Krizsan and and Conny Roggeband, eds., Gendering Democratic Backsliding in Central and Eastern Europe: A Comparative Agenda, Budapest: CEU Press, CPS, 2019, 221 pp., price not listed (ebook), ISBN 978-615-5547-07-2. Ludmila Miklashevskaya, Gender and Survival in Soviet Russia: A Life in the Shadow of Stalin's Terror, translated and edited by Elaine MacKinnon, London: Bloomsbury Academic, 2020, 267 pp., 115.00 (hardback), ISBN: 978-1-3501-3920-6. Barbara Molony and Jennifer Nelson, eds., Women's Activism and "Second Wave" Feminism: Transnational Histories . New York: Bloomsbury Academic, 2017, 344 pp., £90.00 (hardback), ISBN: 978-1-4411-3160-7; 2020, 335 pages, £26.99 (paperback), ISBN: 978-1-3501-2770-8. Nina Konstantinovna Petrova, ed. Zhenskie sud'by voiny (Women's war fates), Moscow: Veche, 2019, 600 pp., P- 655.00 (hardback), ISBN 978-5-4484-0954-7. Feryal Saygılıgil and Nacide Berber, eds. Feminizm: Modern Türkiye'de Siyasi Düşünce, Cilt 10 (Feminism: Thought in modern Turkey, vol. 10), Istanbul: İletişim Yayıncılık A.Ş., 2020; 880 pp., with an extensive bibliography, Index, and annexed section of selected primary texts, 789–880; 71.50 (hardback), ISBN: 978-975-05-0003-9. Marsha Siefert, ed., Labor in State-Socialist Europe, 1945–1989: Contributions to a History of Work, Work and Labor: Transdisciplinary Studies for the 21st Century, vol. 1, Budapest: CEU Press, 2020, xv +466 pp., 105.00 / €90.00 / £85.00 (hardback), ISBN: 978-963-386-337-4. Zilka Šiljak Spahić, Sociologija roda: Feministička kritika (Sociology of gender: Feminist critique), Sarajevo: TPO Fondacija, 2019, 274 pp., €10.00 (paperback), ISBN: 978-9926-422-17-2. Věra Sokolová and Ľubica Kobová, eds., Odvaha nesouhlasit: Feministické myšlení Hany Havelkové a jeho reflexe (The courage to disagree: Hana Havelková's feminist thought and its reflections), Prague: Charles University, Faculty of Humanities, 2019, 605 pp., price not listed (paperback), ISBN: 978-80-7571-038-3. Katarzyna Stańczak-Wiślicz, Piotr Perkowski, Małgorzata Fidelis, Barbara Klich-Kluczewska, Kobiety w Polsce, 1945–1989: Nowoczesność, równouprawnienie, komunizm (Women in Poland, 1945–1989: Modernity, equality, communism), Cracow: Universitas, 2020, 520 pp., 49.00 zł, ISBN: 978-83-242-3630-5; 29.00 zł (e-book), ISBN: 978-83-242-6504-6. Vassiliki Theodorou and Despina Karakatsani, Strengthening Young Bodies, Building the Nation: A Social History of the Child Health and Welfare in Greece (1890–1940), Budapest: Central European University Press, 2019, 374 pp., 95.00 (hardback), ISBN: 978-963-386-278-0. Maria Todorova, The Lost World of Socialists at Europe's Margins: Imagining Utopia, 1870s–1920s, London: Bloomsbury Academic, 2020, 384 pp., 115.00 (hardcover), ISBN: 978-1-350-15033-1. Jessica Zychowicz, Superfluous Women: Art, Feminism, and Revolution in Twenty-First-Century Ukraine, Toronto: University of Toronto Press, 2020, 420 pp., 63.75 (hardcover), ISBN: 978-1-4875-0168-6.